Relationships between Imperfections and Shear Buckling Resistance in Web Plate with Sectional Damage Caused by Corrosion - Jin-Hee Ahn; Shigenobu Kainuma; Won-Hong Lee; Youn-Ju Jeong; In-Tae Kim (Advances in Materials Science and Engineering)
This study deals with the relationship between imperfections and shear buckling resistance of web plates with sectional damage caused by corrosion. To examine the imperfection effect on the shear buckling resistance of a web plate with sectional damage, a series of nonlinear finite element (FE) analyses were carried out for a web plate with sectional damage, which was assumed as local corrosion damage. For considering imperfections of the web plate in the girder, initial out-of-plane deformation was introduced in the FE analysis model. Using the FE analysis results, the changes in the shear buckling resistance of the web plate with sectional damage were quantitatively examined and summarized according to the aspect ratio, boundary conditions, and height of the damaged section of the web plate. The effects of web imperfections on the shear buckling resistance were evaluated to be little compared to that of the web plate without sectional damage. The shear buckling resistance was shown to significantly change in the high-aspect-ratio web plate. A simple evaluation equation for the shear buckling resistance of a web plate with sectional damage was modified for use in the practical maintenance of a web plate in corrosive environments.